Legal Enforcement on Environmental Impact of Palm Oil Plantation of Merauke District - Alputila Jane Marlyn; Waas Rullof F. Y.; Silambi Erni Dwita; Azis Yuldiana Zesa; Tajuddin Mulyadi Alrianto (E3S Web of Conferences, 2018)
Merauke City is one of the cities in Papua which has 4.6 million hectares consisting of 3.1 million hectare for forest coverage and the rest is 1.5 non-forest coverage. Around 66% forest coverage consists of primary forest, high-density secondary forest, low-density secondary forest, primary swamp forest, secondary swamp forest, eucalyptus/acacia forest, primary mangrove forest, and secondary mangrove forests. Merauke City is one of the place which has a great potential to maintain and sustain ecological system with its vast territory and its evergreen forest which people keep its sustainability. However, the government and some companies expanding their business take a toll for the balance of the nature, since some of the forest areas are cut down and the industrial waste affects the ecosystem. Some territories in Merauke become heavily polluted from the wastes. One of the pollution cases is from six palm oil companies which has polluted some forests in Merauke, Papua. The companies responsible for the decreasing environmental condition are operating in Malind Bian such as PT Dongin Prabhawa ( Korindo Group), PT Bio Inti Agrindo (Korindo group), PT Central Cipta Murdaya (CCM), PT Agriprima Cipta Persada, PT Hardaya Sawit Papua and PT Berkat Cipta Abadi. The method is of this study is normative legal approach. The result of this study reveals that the government are advised to include the society and the locals to make a decision and to find a good solution for the environment which has been sustaining their life. This may resolve the problem between the palm oil company, the government, and the society to uphold a new law. The government should be strict to set rules in order to be beneficial not only for the companies, but also for the society, the government, and the environment in Merauke City. When the law has been issued, the companies indicated to be violating certain set of rules regarding environmental pollution and contamination, can be evaluated and revoked of their warrant to do business in Merauke. This will be a good solution to make sure the sustainability of the environment, forests, and the society depending on it.